The epidemiology of cruciate ligament rupture in an insured Swedish dog population - Engdahl, Karolina (Sci Rep, 2021)
Cruciate ligament rupture (CLR) is a common orthopedic disorder in dogs. The study objectives were to evaluate incidence rate (IR), cause-specific mortality rate (CSMR) and risk factors for CLR in insured dogs. A single cohort study of dogs insured in Agria Pet Insurance in Sweden (2011–2016) was performed. Age at diagnosis, IR, CSMR and relative risk (RR) for CLR was calculated overall and per breed. The cohort included just over 600,000 dogs. The IR of CLR was 23.8 (95% confidence interval, 23.1–24.6) cases per 10,000 DYAR. The breeds with highest RR of CLR were Boerboel and Dogo Canario, while the breeds with lowest RR were Standard Dachshund and Miniature Pinscher. Dogue de Bordeaux had highest RR of euthanasia due to CLR. The median age at veterinary care claim for CLR was 7.1 (range 0.3–16.0) years and 6.6 (0.3–12) years at life insurance settlement. Large and giant breeds were generally diagnosed and euthanized due to CLR at a younger age compared to smaller breeds. The majority of the breeds with increased RR of CLR diagnosis and CLR-related euthanasia were large or giant. A pattern of increasing size and decreasing age at diagnosis/CLR-related euthanasia was observed.